Integration of Argumentation Activities in Virtual-Inquiry to Improve Argumentation Skills of Prospective Science Teacher in Basic Physics Courses - Siswanto Siswanto; Bambang Subali; Ellianawati Ellianawati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Argumentation skills are a prominent domain that must be trained for prospective science teacher students. This study aims to determine the effectiveness of science learning which is implemented using virtual inquiry learning in improving the argumentation skills of prospective science teachers. We used a quasi-experimental method with a non-equivalent control class design where researchers divided students into two classes: the experimental class (N = 38) and the control class (N = 38). The learning process in the experiment class was carried out by the virtual-inquiry model which was inserted with scientific argumentation activities, while in the control class, the learning process was carried out using the virtual-inquiry model without inserting scientific argumentation activities. All students involved in the research were given a test to measure argumentation skills between before and after the learning process. Argumentation skills are analyzed in two aspects, namely the completeness of organs and the scientific aspect. Data were analyzed by categorizing each student's answer into each aspect of argumentation skills, both before and after the learning process. After that, the mean difference significance test was carried out. Then, n-gain was used to analyze the increase of argumentation skill. The results indicate that the virtual-inquiry model which was inserted by argumentation activities was better at improving the argumentation skills of prospective science teachers compared to the virtual inquiry model without being inserted by argumentation activities. In the experimental class, the increase in argumentation skills showed high criteria. These results were obtained both on the aspect of organ completeness and the scientific aspect. Meanwhile, in the control class, it is in the low category for the aspect of organ completeness and is in the moderate category for the scientific aspect. These findings indicate that in scientific argumentation training, it is very important to involve students to practice argumentation directly.Keywords: virtual-inquiry, argumentation skill, scientific aspect of argumentation, organ completeness aspect of argumentation